Is traditional budgeting still relevant? / Rosiatimah Mohd Isa - Mohd Isa, Rosiatimah (Universiti Teknologi MARA, Perlis, 2005)
The traditional budgeting process operates within the traditional hierarchical 'command and control model'. It is recognized as a major barrier to change companies that wish to devolve responsibility and respond more quickly to competitive threats and opportunities. In the new management model that leads to more flexible approach, the traditional budgeting has become less relevance. Many large companies have replaced their budgeting system in whole or in part with alternative mechanisms.